CONSUMER LENDING BUSINESS PROCESSES FOR BANKING AND NON-BANKING FINANCIAL INSTITUTIONS: CORE DIFFERENCES - KAMINSKYI, Andrii; PYSANETS, Kostiantyn; PETROVSKYI, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article explores the fundamental distinctions between banks and non-bank financial institutions in the consumer lending sector, emphasizing Make-and-Sell (M/S) and Sense-and-Respond (S/R) business strategies. To define these strategies, four key criteria were analyzed: “profit focus,” “know-how,” “general business process,” and “organizational priority.” Banks traditionally adopt a structured M/S approach that prioritizes long-term planning and standardized processes. In contrast, non-bank financial institutions use the adaptive S/R strategy, characterized by flexibility, modular customization, and rapid innovation. These institutions emphasize agility in responding to customer needs and utilize advanced technologies to optimize their processes. The research highlights how these differences impact customer relationship management (CRM) processes and credit risk assessment. Banks primarily rely on traditional credit scoring models, classifying borrowers into "good" or "bad" categories based on their delinquency. In contrast, non-bank financial institutions adopt a segmented approach based on profitability. This segmentation, represented through the Whale curve, allows non-bank institutions to identify high-profit clients and tailor strategies to maximize returns. The difference is also present in the usage of credit bureau data. The findings underscore the dual impact of fintech innovation on financial stability. While non-bank financial institutions have expanded access to credit and driven innovation, they operate in higher-risk environments with less regulatory oversight, contributing to potential financial instability. Conversely, banks face increasing competitive pressures, necessitating the adaptation of rigid traditional processes to remain viable in this evolving landscape.